Antimycobacterial Metabolites from Marine Invertebrates. Issue 10 (26th August 2016) - Daletos, Georgios; Ancheeva, Elena; Chaidir, Chaidir; Kalscheuer, Rainer; Proksch, Peter
Abstract : Marine organisms play an important role in natural product‐based drug research due to accumulation of structurally unique and bioactive metabolites. The exploration of marine‐derived compounds may significantly extend the scientific knowledge of potential scaffolds for antibiotic drug discovery. Development of novel antitubercular agents is especially significant as the emergence of drug‐resistant Mycobacterium tuberculosis strains remains threateningly high. Marine invertebrates (i.e., sponges, corals, gorgonians) as a source of new chemical entities are the center of research for several scientific groups, and the wide spectrum of biological activities of marine‐derived compounds encourages scientists to carry out investigations in the field of antibiotic research, including tuberculosis treatment. The present review covers published data on antitubercular natural products from marine invertebrates grouped according to their biogenetic origin. Studies on the structure–activity relationships of these important leads are highlighted as well. Abstract : Tuberculosis remains one of the world's most lethal infectious diseases. Marine organisms represent a prolific source of structurally unique compounds that can be utilized in the search for new antitubercular drugs from nature. This review covers antimycobacterial metabolites derived from marine invertebrates with available data on structure–activity relationships and mechanism‐of‐action studies.